Risks of breast or ovarian cancer in BRCA1 or BRCA2 predictive test negatives: findings from the EMBRACE study. (December 2018) - Girardi, Fabio; Barnes, Daniel; Barrowdale, Daniel; Frost, Debra; Brady, Angela; Miller, Claire; Henderson, Alex; Donaldson, Alan; Murray, Alex; Brewer, Carole; Pottinger, Caroline; Evans, D Gareth; et al.
Abstract Purpose BRCA1/BRCA2 predictive test negatives are proven noncarriers of aBRCA1/BRCA2 mutation that is carried by their relatives. The risk of developing breast cancer (BC) or epithelial ovarian cancer (EOC) in these women is uncertain. The study aimed to estimate risks of invasive BC and EOC in a large cohort ofBRCA1/BRCA2 predictive test negatives. Methods We used cohort analysis to estimate incidences, cumulative risks, and standardized incidence ratios (SIRs). Results A total of 1, 895 unaffected women were eligible for inclusion in the BC risk analysis and 1, 736 in the EOC risk analysis. There were 23 incident invasive BCs and 2 EOCs. The cumulative risk of invasive BC was 9.4% (95% confidence interval (CI) 5.9–15%) by age 85 years and the corresponding risk of EOC was 0.6% (95% CI 0.2–2.6%). The SIR for invasive BC was 0.93 (95% CI 0.62–1.40) in the overall cohort, 0.85 (95% CI 0.48–1.50) in noncarriers fromBRCA1 families, and 1.03 (95% CI 0.57–1.87) in noncarriers fromBRCA2 families. The SIR for EOC was 0.79 (95% CI 0.20–3.17) in the overall cohort. Conclusion Our results did not provide evidence for elevated risks of invasive BC or EOC inBRCA1/BRCA2 predictive test negatives.